2016
DOI: 10.1016/j.ceramint.2016.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric characterization of microwave sintered lead zirconate titanate ceramics

Abstract: Highly reactive lead zirconate titanate powders (PZT) with different compositions were successfully synthesized by the oxidant-peroxo method (OPM) and used to prepare dense ceramic samples with composition near to the morphotropic phase boundary (MPB) sintered at 1000°C for 2 h using a tubular conventional oven and a commercial microwave system. Crystalline phases were identified in the powder and ceramic samples by X-ray powder diffraction and FT-Raman spectroscopy at room temperature. The fractured surface o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…PZT sintered at 935 °C has a tetragonal crystal structure with a P4mm space group. Goncalves et al 17 also reported a similar Rietveld refinement are listed in Table 2. The reliability parameters are listed in Table S1 of the Supporting Information.…”
Section: ■ Experimental Sectionmentioning
confidence: 57%
See 1 more Smart Citation
“…PZT sintered at 935 °C has a tetragonal crystal structure with a P4mm space group. Goncalves et al 17 also reported a similar Rietveld refinement are listed in Table 2. The reliability parameters are listed in Table S1 of the Supporting Information.…”
Section: ■ Experimental Sectionmentioning
confidence: 57%
“…Figure illustrates the schematic diagram of the microwave furnace and the pictorial representation of the working principle self-heating process . Previously, there are several reports of microwave-sintered modified PbTiO 3 and BaTiO 3 . , …”
Section: Introductionmentioning
confidence: 99%
“…[41] The polarization characteristics of the ceramic dielectrics are nonlinear due to a wider particle size distribution and presence of impurities, arising as a result of heterogeneous mixing during ceramic powder synthesis. [42,43] As a result of this nonlinearity, ceramic dielectric permittivity, a material property that determines the extent of polarization of the ceramic molecules under the influence of electric field, eventually turns nonhomogeneous.…”
Section: Challenges Associated With Heterogeneous Materials Propertiesmentioning
confidence: 99%
“…In addition to searching for new types of multiferroic materials, an intensive search for effective technological methods for their production (synthesis and sintering) to meet these unique requirements has been underway [ 1 , 4 ]. Numerous synthesis methods of ceramic materials are known, e.g., solid-state reaction technique [ 5 , 6 , 7 , 8 ], calcination [ 9 , 10 , 11 , 12 , 13 ], sol-gel [ 14 , 15 ], gel-combustion [ 16 ], mechanochemical activation [ 17 , 18 , 19 , 20 ], and the self-developing synthesis of SHS [ 21 , 22 ], as well as sintering methods, e.g., free sintering (pressureless sintering) [ 23 ], hot pressing [ 24 , 25 , 26 ], microwave sintering [ 23 , 27 , 28 ], spark plasma sintering SPS [ 29 , 30 , 31 , 32 ], and cold-sintering-assisted sintering CSS [ 33 , 34 ]. Well-known methods of synthesis and sintering are used to improve the functional properties of multiferroic materials, which are appropriately modified and combined in the technological process.…”
Section: Introductionmentioning
confidence: 99%